Survey of MapReduce on Big Data (International Journal of Engineering and Computer Science, 2017)
As of recent trends, this is a persistent challenge of integration of cloud computing, data mining and big data mining processes. This paper reveals most recent progress on Hadoop and MapReduce applications. Hadoop and MapReduce can be used for analyzing enormous amount of data. Hadoop is an open source software project used to processing a large data sets. MapReduce is a programming model that associated implementation for parallel processing of large dataset. Big data environment is used to acquire, organize and analyze the various types of data. There is an observation about MapReduce framework. This framework generates large amount of intermediate data.